Reações entre ácidos β-cianocarboxílicos e nitrogênios nucleofílicos: uma eficiente estratégia para a síntese de succinimidas, pirrolidinonas e tetrazóis - Silva, Fabio Machado da (2011)
This work presents the synthesis of 41 succinimides, 24 pyrrolidinones and 8 tetrazoles, all presenting unprecedented chemical structure, except for the succinimide 3-ethoxy-1-methylpyrrolidine-2,5-dione. These compounds were synthesized by cyclization reactions of β-cyanocarboxylic acids of general formula HO2CCH(R1)CH(OR)CN, where R/R1 = Et/H (9), -(CH2)2- (10), -(CH2)3- (11), Et/Me (12), i-Pr/H (13), s-Bu/H (14), i-Pr/Me (15), s-Bu/Me (16), with amine derivatives or sodium azide. Initially NR2-substituted 3-ethoxypyrrolidine-2,5-diones were obtained from the cyclization of 3-ethoxy-3-cyanopropanoic acid 9 with a series of amine derivatives of general formula NH2R2, where R2 = -CH2-2-Py (17a), -CH2-3-Py (17b), -CH2-4-Py (17c), -CH2C6H5 (17d), -(CH2)2C6H5 (17e), -(CH2)2NMe2 (17f), -(CH2)2NEt2 (17g), Me (17h), Et (17i), Pr (17j), i-Pr (17k), allyl (17l), -(CH2)2OH (17m), -(CH2)3OH (17n), - CH2CH(OH)Me (17o), -CH(CH2OH)Et (17p), -CH(CH2OH)i-Pr (17q), -CH(CH2OH)i-Bu (17r), -CH(CH2OH)s-Bu (17s), -CH(CH2OH)Bn (17t), -CH2CO2H (17u) e - CH2CONH2 (17v). When the cyclization reaction were carried out with diamines of structure NH2(CH2)nNH2, where n = 1, 2 ou 3, the corresponding 1,1 -(alkyldiyl)bis(3- ethoxypyrrolidine-2,5-diones) were obtained. In addition, the reaction of 2-cyanotetrahydrofuran-3-carboxylic acid 10 with amines 17a-p, furnished a series of NR2- substituted 2,3,3a,6a-tetrahydrofuro[2,3-c]-5H-pyrrol-4,6-diones in good yields. In sequence, 4-ethoxy-5-hydroxypyrrolidin-2-ones and 6-hydroxy-3,3a,6,6atetrahydro- 2H-furo[2,3-c]-5H-pyrrol-4-ones were synthesized by regioselective reduction of 3-ethoxypyrrolidine-2,5-diones and 2,3,3a,6a-tetrahydrofuro[2,3-c]-5Hpyrrol- 4,6-diones, previously obtained, by reaction of acids 9 and 10 with selected nucleophiles 17a-l. The reduction reactions were performed using sodium borohydride as reducing agent and, in general, the hydroxylated products were obtained with high diastereoselectivity. Finally, [2 + 3] cycloaddition reaction between β-cyanocarboxylic acids 9-16 with sodium azide, catalyzed by zinc chloride, were carried out furnishing a series of 5-substituted 1-H tetrazoles, where R/R1 = Et/H, -(CH2)2-, -(CH2)3-, Et/Me, i-Pr/H, s- Bu/H, i-Pr/Me, s-Bu/Me.